2015
DOI: 10.1371/journal.pone.0118988
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Salmon Usage of the Skeena River Estuary

Abstract: Migratory salmon transit estuary habitats on their way out to the ocean but this phase of their life cycle is more poorly understood than other phases. The estuaries of large river systems in particular may support many populations and several species of salmon that originate from throughout the upstream river. The Skeena River of British Columbia, Canada, is a large river system with high salmon population- and species-level diversity. The estuary of the Skeena River is under pressure from industrial developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 46 publications
(61 reference statements)
1
27
0
Order By: Relevance
“…Previous research mapping juvenile salmon use of estuary regions found particularly high abundances of juvenile sockeye, Chinook, and coho salmon near the Skeena River mouth, around the Lelu Island and Flora Bank region (Figure ) (Carr‐Harris et al, ). In addition, this area supports more than 40 populations of sockeye and Chinook salmon from throughout the Skeena River watershed (Carr‐Harris et al, , ; Moore, Carr‐Harris, Gottesfeld, et al, ) and encompasses the locations of seven of the eight LNG developments that were proposed for the greater Skeena River estuary (Aurora LNG, ; Exxon Mobil, ; Pacific Northwest LNG, ; Pembina Pipeline, ; Prince Rupert LNG Ltd, ; Province of British Columbia, , ). This study builds on these previous findings to examine how salmon and other pelagic fish are using specific estuary habitat types and locations.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…Previous research mapping juvenile salmon use of estuary regions found particularly high abundances of juvenile sockeye, Chinook, and coho salmon near the Skeena River mouth, around the Lelu Island and Flora Bank region (Figure ) (Carr‐Harris et al, ). In addition, this area supports more than 40 populations of sockeye and Chinook salmon from throughout the Skeena River watershed (Carr‐Harris et al, , ; Moore, Carr‐Harris, Gottesfeld, et al, ) and encompasses the locations of seven of the eight LNG developments that were proposed for the greater Skeena River estuary (Aurora LNG, ; Exxon Mobil, ; Pacific Northwest LNG, ; Pembina Pipeline, ; Prince Rupert LNG Ltd, ; Province of British Columbia, , ). This study builds on these previous findings to examine how salmon and other pelagic fish are using specific estuary habitat types and locations.…”
Section: Methodsmentioning
confidence: 94%
“…A 2‐year field study of juvenile salmon and pelagic species and their habitats was conducted in the Skeena River estuary in 2015 and 2016. This research is part of a collaborative research programme with the Lax Kw'alaams Fisheries Program, Skeena Fisheries Commission, and Simon Fraser University examining the estuary phase of juvenile salmon migration in the Skeena River (Arbeider, Sharpe, Carr‐Harris, & Moore, ; Carr‐Harris et al, ; Carr‐Harris, Gottesfeld, & Moore, ; Moore et al, ; Moore, Carr‐Harris, Gottesfeld, et al, ). Previous research mapping juvenile salmon use of estuary regions found particularly high abundances of juvenile sockeye, Chinook, and coho salmon near the Skeena River mouth, around the Lelu Island and Flora Bank region (Figure ) (Carr‐Harris et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Weekly trawl samples were collected at six sites in the estuary of the Skeena River from the beginning of May until the beginning of July in both years (Carr‐Harris et al. ; Moore et al. ).…”
Section: Methodsmentioning
confidence: 99%